1987
DOI: 10.2337/diacare.10.4.441
|View full text |Cite
|
Sign up to set email alerts
|

Small- and Large-Fiber Involvement in Early Diabetic Neuropathy: A Study With the Medial Plantar Response and Sensory Thresholds

Abstract: Small- and large-fiber function in diabetic neuropathy was studied in 68 patients (mean age 45.4 +/- 12.9 yr; 27 type I and 41 type II diabetics) with psychophysical tests of vibration and thermal sensation and neurophysiological measurements, including the medial plantar sensory action potential (MPSAP). Thermal sensitivity at the dorsolateral aspect of the foot (Pfizer thermal tester) correlated significantly with vibration thresholds (Somedic vibrameter) at three sites in the foot and two in the hand. Forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
3

Year Published

1990
1990
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 0 publications
0
35
0
3
Order By: Relevance
“…Most of these studies used a hand-held instrument (bioesthesiometer) which is known to lack reproducibility. Levy et al 23 reported a coefficient of variation of 0.46 for thermal and 0.40-0.65 for vibratory threshold on three repeated testings. Kenshalo and BergenI8 reported a pronounced intraindividual consistency of thermal testing in a few well-trained subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies used a hand-held instrument (bioesthesiometer) which is known to lack reproducibility. Levy et al 23 reported a coefficient of variation of 0.46 for thermal and 0.40-0.65 for vibratory threshold on three repeated testings. Kenshalo and BergenI8 reported a pronounced intraindividual consistency of thermal testing in a few well-trained subjects.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques do not evaluate small fiber, which conduct autonomic function, sense cold, heat, and pain, and are altered earlier than thick fiber in DM patients and glucose intolerants. 15,[16][17][18][19][20] Hence our interest in comparing DSPN frequency in T2DM patients by using two different methods: (1) thermal threshold (TT) which studies small fiber function and (2) EMG and NC, which study large fiber function.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological testing led to the detection of abnormalities in a majority of patients with diabetes, even in patients who were free of neurological symptoms and of definite signs on the physical neurological examina- tion [13,1]. However, this study emphasized important differences concerning the development and course of diabetic neuropathy between LADA and type 2 diabetes patients.…”
Section: Discussionmentioning
confidence: 77%
“…Several tests are available for obtaining more quantitative information about the involvement of different types of nerve fibres [13]. Nerve conduction studies are useful for large myelinated motor and sensory nerve fibres.…”
Section: Introductionmentioning
confidence: 99%